2020
DOI: 10.1021/acsami.0c12695
|View full text |Cite
|
Sign up to set email alerts
|

Self-Protonated Ho-Doped Zn(O,S) as a Green Chemical-Conversion Catalyst to Hydrogenate Nitro to Amino Compounds

Abstract: Zn(O,S) has been successfully doped with different amounts of Ho and characterized with X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), electrochemical impedance spectroscopy (EIS), and transient photocurrent (TPC). The as-prepared Ho-doped Zn(O,S) catalysts with different Ho amounts are evaluated for hydrogen evolution reaction. The catalyst with the best performance in evolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Figure f shows that the S 2p 3/2 and 2p 1/2 orbitals are observed at 163.19 and 163.33 eV, respectively, with a separation energy of 1.14 eV between them. The peak positions of S 2p agreed well with previous works. , The XPS compositional analysis is done based on the peak area in the high-resolution spectra of elements, and the results are shown in Table .…”
Section: Results and Discussionsupporting
confidence: 85%
“…Figure f shows that the S 2p 3/2 and 2p 1/2 orbitals are observed at 163.19 and 163.33 eV, respectively, with a separation energy of 1.14 eV between them. The peak positions of S 2p agreed well with previous works. , The XPS compositional analysis is done based on the peak area in the high-resolution spectra of elements, and the results are shown in Table .…”
Section: Results and Discussionsupporting
confidence: 85%
“…based materials have been proved achieving a great effect on hydrogenation of nitroaromatic compounds at ambient temperature. 14,15 As earth-abundant and inexpensive metal, Cu has been frequently investigated as alternative to rare metal materials, especially in catalysis. 16 Cu based nanomaterials are particularly attractive due to their improving catalytic activity effectively.…”
Section: Introductionmentioning
confidence: 99%
“…based materials have been proved achieving a great effect on hydrogenation of nitroaromatic compounds at ambient temperature. 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for CZ-5 and CZ-10 nanocatalysts, Co might be precipitated on the catalyst surfaces due to the excess amount of Co, thus resulting in less effective doping of Co at the Zn cation site in the Zn(O,S) structure. 29 The diffractogram also confirmed that the as-prepared CZ-x nanocatalyst possessed no secondary phase.…”
Section: Solar Light Photocatalytic Hydrogen Evolution Reaction (Her)mentioning
confidence: 57%
“…Besides, it was found that the doping of Co at 2.5% induced the maximum shift, indicating the most optimum dopant amount of Co into the Zn­(O,S) lattice. Meanwhile, for CZ-5 and CZ-10 nanocatalysts, Co might be precipitated on the catalyst surfaces due to the excess amount of Co, thus resulting in less effective doping of Co at the Zn cation site in the Zn­(O,S) structure . The diffractogram also confirmed that the as-prepared CZ- x nanocatalyst possessed no secondary phase.…”
Section: Results and Discussionmentioning
confidence: 80%